Business Faculty in Canadian Universities: Importance and Satisfaction Related to Job Characteristics - Hurka, Slavek J. (Canadian Journal of Higher Education, 1978)
This paper examines the relationship between the importance and satisfaction of various job characteristics as perceived by 322 business faculty members teaching in 15 Canadian universities. The findings suggest that those aspects which the respondents felt to be most important were also those with which they were the least satisfied.